2001
DOI: 10.1248/bpb.24.1072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mosapride Citrate on Human Plasma Levels of Motilin, Gastrin, Somatostatin, and Secretin.

Abstract: Mosapride citrate (mosapride) (4-amino-5-chloro-2-ethoxy-N-{[4-(4-fluorobenzyl)-2-morpholinyl]methyl}benzamidecitrate) is a novel gastroprokinetic agent that enhances gastrointestinal motility by stimulating the serotonin (5-HT 4 ) receptor. 1) This agent stimulates acetylcholine release from cholinergic neurons in the gastrointestinal wall and may enhance upper gastrointestinal motor activity in the postprandial state in conscious dogs. 2) We previously confirmed that cisapride causes significant increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Alternatively, the lack of a significant difference of t max in this study may be due to time of dosing of mosapride since we gave mosapride 1 h before omeprazole in the previous study while mosapride was taken concomitantly in this study. The maximal prokinetic effects of mosapride occur within 0.5– 1 h [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the lack of a significant difference of t max in this study may be due to time of dosing of mosapride since we gave mosapride 1 h before omeprazole in the previous study while mosapride was taken concomitantly in this study. The maximal prokinetic effects of mosapride occur within 0.5– 1 h [12]. …”
Section: Discussionmentioning
confidence: 99%
“…They showed reduced resolution and it hampered their accurate determination. The addition of HSA, the hydrophobic ionpair reagent, is particularly useful for the separation and detection of several drugs, such as nabumetone 15) and mosapride, 16) because it provides appropriate capacity factors for complexes formed with the counterion. When the effects of HSA concentration were examined, as shown in Fig.…”
Section: Optimization Of the Chromatographic Systemmentioning
confidence: 99%
“…Itoh et al reported that cisapride, a dopamine D 2 receptor antagonist and nonselective serotonin 5-HT 1, 3, 4 receptor agonist, induced a rise in plasma levels of motilin, gastrin and somatostatin, 5) while mosapride, a selective serotonin 5-HT 4 agonist, raised motilin and gastrin 6) plasma levels. We have investigated the effects of Sho-hange-ka-bukuryo-to, which is a Kampo medicine closely related to Nichin-to, on plasma gut-regulatory peptide levels.…”
Section: Introductionmentioning
confidence: 99%